Public communication by climate scientists: what, with whom and why? - Entradas, M.; Marcelino, J.; Bauer, M. W.; Lewenstein, B. (Climatic Change, 2019)
Public communication of science has increasingly been recognised as a responsibility of scientists (Leshner, Science p. 977, 2003). Climate scientists are often reminded of their responsibility to participate in the public climate debate and to engage the public in meaningful conversations that contribute to policy-making (Fischhoff 2013). However, our understanding about climate scientists’ interactions with the public and the factors that drive or inhibit them is at best limited. In a new study, we show that it is the most published and not necessarily the most senior, which often talk in public, and it is primarily intrinsic motivation (as opposed to extrinsic reward), which drive them to engage in public communication. Political orientations, academic productivity and awareness of controversy, the topic raises in the public domain, were also important determinants of a climate’s scientist public activity. Future research should explore what is required to protect the intrinsic motivation of scientists.